2019
DOI: 10.1161/circulationaha.118.034757
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine γ Lyase Sulfhydrates the RNA Binding Protein Human Antigen R to Preserve Endothelial Cell Function and Delay Atherogenesis

Abstract: -Hydrogen sulfide (HS), generated by cystathionine γ lyase (CSE), is an important endogenous regulator of vascular function. The aim of the present study was to investigate the control and consequences of CSE activity in endothelial cells under physiological and pro-atherogenic conditions. -Endothelial cell CSE knock out mice were generated and lung endothelial cells were studied (gene expression, protein sulfhydration and monocyte adhesion). Mice were crossed onto the ApoE background and atherogenesis (partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 39 publications
9
87
0
1
Order By: Relevance
“…Interestingly, aortic valves with calcification expressed more CSE but produced less H 2 S. Although not directly tested in the study, it is possible that CSE in calcified tissue is hyperphosphorylated on S377, leading to reduced activity. A similar finding has been recently reported for CSE in atheromas (Bibli et al, ). Based on their findings, the authors proposed that H 2 S donors might be useful in the treatment of valve calcification.…”
supporting
confidence: 91%
“…Interestingly, aortic valves with calcification expressed more CSE but produced less H 2 S. Although not directly tested in the study, it is possible that CSE in calcified tissue is hyperphosphorylated on S377, leading to reduced activity. A similar finding has been recently reported for CSE in atheromas (Bibli et al, ). Based on their findings, the authors proposed that H 2 S donors might be useful in the treatment of valve calcification.…”
supporting
confidence: 91%
“…In keeping with our hypothesis that CAVD is a condition of perturbed H 2 S bioavailability, we found a deficiency in the generation of H 2 S in human AS valves in spite of the elevated expression of CSE. This contradiction can be resolved by the observations of Bibli et al, (2019), who found a markedly decreased H 2 S production after phosphorylation of Ser 377 of CSE, resulting in enzyme inactivation. As such, therapeutic supplementation of H 2 S using H 2 S donor molecules such as AP72 or other novel compounds that are currently under preclinical or clinical investigation by us and others may offer a novel approach to prevent valvular calcification in CAVD and related conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, more studies support that H 2 S could inhibit the process of endothelial cell inflammation (Wen et al, 2018). For instance, specific endothelial deletion of CSE is associated with the development of endothelial inflammation and atherosclerosis, effects that are reversed on treatment with a polysulfide donor (Bibli et al, 2019). H 2 S treatment reduces the increases in inflammatory mediators such as vascular cell adhesionmolecule-1 (VCAM-1), intercellular adhesionmolecule-1 (ICAM-1) and monocyte chemoattractant protein-1 (MCP-1) in endothelial cell induced by tumour necrosis factor-a (TNF-a), and the underlying mechanism of this protective effect is primarily mediated by inhibition of soluble TNF-a shedding and its relevant MCP-1 release (Perna et al, 2013).…”
Section: Role Of H 2 S In Endothelial Inflammationmentioning
confidence: 99%